Perceptions of Teachers towards Assessment Techniques at Secondary Level Private School of Karachi - Henna Fatemah (Journal of Education and Educational Development, 2020)
This paper sets out to explore the perceptions of teachers towards assessment techniques at a secondary level private school of Karachi. This was conjectured on the basis of the circumstances of parallel boards in the education system of Pakistan and its effectiveness within the context with respect to the curriculum. This was gauged in line with the forms and techniques of assessment corresponding with the curriculum. A qualitative research design based on interviews was chosen for this study. Purposive sampling was used to select the teachers from a school. The findings of the study revealed that the General Certificate of Secondary Education (GCSE) is best suited to assess students’ knowledge and skills and the teachers viewed that in order for students to be accomplished in this board, the ways of assessment must take a more meaningful measure of evaluating student’s progress.
Keywords: assessment techniques, curriculum, GCSE, secondary leve; assessment techniques; curriculum; GCSE; secondary leve